Feasibility study on using MCDM for e-voting - Rozlina, Mohamed; Ng, Suit Yan (Penerbit UMP, 2022)
An online voting system is an election system that manages the election process. This is a medium for the voters to cast their votes. It is also being used to calculate the votes collected from the voters to choose the representative for their own faculty. A typical voting system is based on a single attempt for each candidate being voted. The voting does not reflect the criteria implies to the characteristic of the candidate that going to be the student leader. To be a student leader, the student should fulfil the requirement such as good academic results, interpersonal skills with society, involving in activities of university and etc. Although the current voting system is able to maximize the participation of the voters, the voters may blindly vote the ballots casually due to they do not know the details of the candidates and the result is low quality and low public’s trust in the selected candidate. In this study, the aim is to develop an interactive online voting system that have ranking feature with MCDM method which allow online voting system to collect high-quality results from the voters. The Multiple Criteria Decision Making (MCDM) method is used in the voting system while choosing the candidate. MCDM can let the voters make decision making or selecting the candidate based on the criteria that suit the position. The study starts with the literature study on implementing MCDM for a voting system. Then, a survey will be made to get the users’ views on the with and without implementation of the MCDM method in an online voting system. The expected result of the study is to investigate the current implementation of MCDM as a tool for decision making, then identify the possibility of adopting MCDM for the online voting system while choosing the representative for faculty students’ society. As a conclusion from the survey from the users’ views, it shown that most of the users thinks that the system with the implementation with MCDM method is less time consuming and able to produce high quality result conpare to the current online voting system. Most of the respondents also stated that they are more preferring to use the online voting system with MCDM method in the future.